Hands of time : plein été - De Wilde, Johan, ....-; We Document Art; Universiteitsbibliotheek Gent; Pauwels, Dirk, 1945-; Fauconnier, Maxime; Derycke, Luc, 1963-; Wille, Jeroen; Van den Braembussche, Viktor; Wigman, Menno, 1966-2018 (Gent : MER.paperkunsthalle, 2017)
Een vervolg op "Hands of time": het werk van Johan De Wilde bestaat uit gelaagde tekeningen.
Five years on and the acclaimed 'Hands of Time' has a sequel entitled 'Hands of Time ? Plein été'. The second part is an overview of drawings and other works from the period 2012 to 2017 and follows on seamlessly from the first. Johan De Wilde's work seems, if ever that is possible, to have become even more intense and his drawing style to explore new layers. The drawings can be seen as the work of a human printer (man created the computer in his own image). They are built up like paintings: a labour-intensive process, layer upon layer of horizontal and vertical lines interwoven with a form, a figure. It is as if he is drawing the canvas on which he paints with his pencils. Johan De Wilde draws real time on a scale of 1:1. While his and our time slips by, lines appear, which is another reason why almost every drawing is given the title 'History + a number. Vita brevis, ars longa.'
Het gedicht Aarde, wees niet streng (Menno Wigman, p. 326) werd op 23 april 2012 uitgesproken bij de 144ste eenzame uitvaart te Amsterdam en verscheen in de bundel Slordig met geluk (Uitgeverij Prometheus, Amsterdam, 2015)
Werken van 2012-2017